Simulation Model as an Element of Sustainable Autonomous Mobile Robot Fleet Management - Magdalena Dobrzańska; Paweł Dobrzański (Energies)
Computer simulations of processes are increasingly used in business practice to improve the results of an enterprise and maximise its value. Designing process models and simulating their behaviour provide the opportunity to analyse economic and operational results before appropriate organisational, location, and investment decisions are made. This article presents the possibilities of using simulation modelling in intralogistics systems. In the presented article, a decision-making support tool based on the DES simulator developed by the authors was proposed. This tool supports the decision-making process based on the analysis of parameters that affect the energy efficiency of the analysed process and its sustainability. The possibilities of the proposed tool were presented by giving an example of the analysis of the implementation of the automation of intralogistics processes. As part of the implementation, the use of Autonomous Mobile Robot (AMR) vehicles was proposed. By conducting experiments of the intralogistics system model and analysing the obtained results also in terms of energy consumption by AMR vehicles, the proposed project can be verified and improvements can be proposed. The results obtained in this research confirmed the possibility of using the proposed tool for supporting the decision-making process for assessing the energy efficiency of the designed intralogistics system. The proposed method is a cost-free element of analysis that helps the management staff of a given enterprise make appropriate decisions.